NMR Metabolic Profiling of Sargassum Species Under Different Stabilization/Extraction Processes. Issue 2 (24th February 2021) - Hernández‐Bolio, Gloria Ivonne; Fagundo‐Mollineda, Adrián; Caamal‐Fuentes, Edgar Emmanuel; Robledo, Daniel; Freile‐Pelegrin, Yolanda; Hernández‐Núñez, Emanuel
Abstract : The genus Sargassum is well represented by benthic and pelagic species, some of which form massive aggregates that can travel long distances due to the force of the ocean currents. Although they constitute an essential habitat for fish and invertebrate species, large accumulations of Sargassum in coastal areas generate several economic, environmental, and health impacts. It is important to recognize the species forming these aggregates, and identify the metabolites they produce, allowing for its exploitation, and therefore, better management practices. NMR metabolic profiling is a technique that can discriminate samples while detecting their unique or differential chemical features, and has been successfully used in the study and classification of several algal species. The present investigation studied the metabolic profiling of Sargassum species found on strandings at Puerto Morelos (Quintana Roo) east coast of the Mexican Caribbean. PCA of the 1 H‐NMR profiles corresponding to S. natans, S. natans (morphotype VIII), S. fluitans, and a benthic Sargassum buxifolium allowed the discrimination of samples amongst them. Furthermore, discrimination between the two forms of S. natans was also possible. The PCA loading plot revealed that glutamine and glutamate have the highest influence in the clustering of the benthic Sargassum, while a high abundance of lactate, Myo‐inositol, and trimethylamine is a unique feature from the S. natans morphotype VIII. Additional PLS‐DA models showed that a heat‐drying process improved the extraction of metabolites. Maceration and microwave‐assisted extraction with water‐ethanol led to similar profiles and thus any of them could be used in future investigations.